2020
DOI: 10.3390/jcm9010223
|View full text |Cite
|
Sign up to set email alerts
|

Anti-PD-1 and Novel Combinations in the Treatment of Melanoma—An Update

Abstract: Until recently, distant metastatic melanoma was considered refractory to systemic therapy. A better understanding of the interactions between tumors and the immune system and the mechanisms of regulation of T-cells led to the development of immune checkpoint inhibitors. This review summarizes the current novel data on the treatment of metastatic melanoma with anti-programmed cell death protein 1 (PD-1) antibodies and anti-PD-1-based combination regimens, including clinical trials presented at major conference … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
84
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(86 citation statements)
references
References 72 publications
0
84
0
2
Order By: Relevance
“…Preclinical and clinical data suggest that RT can cause disruption of the blood-brain barrier, enhancing drug delivery to the brain. Moreover, RT may increase the antitumor response by promoting antigen presentation and T-cell activation [45]. 5-ALA PDT can activate an otherwise quiescent local immune response under certain circumstances [46][47][48][49].…”
Section: Discussionmentioning
confidence: 99%
“…Preclinical and clinical data suggest that RT can cause disruption of the blood-brain barrier, enhancing drug delivery to the brain. Moreover, RT may increase the antitumor response by promoting antigen presentation and T-cell activation [45]. 5-ALA PDT can activate an otherwise quiescent local immune response under certain circumstances [46][47][48][49].…”
Section: Discussionmentioning
confidence: 99%
“…It was already reported that in NCT02983045 phase 1/2 trial of Nivolumab + BEMPEG (pegIL-2) 38 patients have been recruited and 53% ORR was achieved. In NCT01968109 phase 1/2 trial of Nivolumab with BMS-986,016 (anti-LAG-3) 43 anti-PD-1 refractory patients we recruited and obtained 16% ORR [110].…”
Section: Expert Opinionmentioning
confidence: 99%
“…Tumore nutzen möglicherweise diese Immuncheckpoint-Moleküle, die eine Schlüsselrolle für die Aufrechterhaltung der Selbsttoleranz unter physiologischen Bedingungen spielen, um der Immunantwort zu entgehen. Daher könnte die Hemmung dieser Interaktionen antitumorale Immunreaktionen in Gang setzen [14]. Ferner hat sich gezeigt, dass die Kombination von Anti-CTLA-4- und Anti-PD-1-Antikörpern synergistisch wirkt, indem sie zu einer Expansion der aktivierten CD8-T-Effektorzellen führt [15, 16].…”
Section: Einführungunclassified